2017
DOI: 10.3126/jsan.v4i1.17377
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative anxiety amongst patients in a tertiary care hospital in India- a prevalence study

Abstract: Background: The prospect of undergoing surgery under anaesthesia can induce significant anxiety in patients. Excess anxiety can lead to several deleterious effects like perioperative cardiac events, increased anaesthetic requirements, higher postoperative pain scores and prolonged hospital stay. Various factors can influence the anxiety levels during surgery. The aim of the study was to estimate the prevalence of anxiety in adult patients scheduled for surgery in a suburban teaching institute in India where th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 16 publications
1
25
1
Order By: Relevance
“…The current finding is higher than the study from China [21], Saudi Arabia [22], India [13] and Iran [9].…”
Section: Discussioncontrasting
confidence: 90%
“…The current finding is higher than the study from China [21], Saudi Arabia [22], India [13] and Iran [9].…”
Section: Discussioncontrasting
confidence: 90%
“…The preoperative anxiety among surgical patients is not routinely performed as part of preoperative patient evaluation and preparation for Anesthesia and surgery (5,(74)(75)(76)(77). However, body of evidences revealed that preoperative anxiety contributed a huge impact on perioperative undesirable outcomes including increased doses of induction agents (11,22,78,79), hemodynamic instability (11,22,27,52,79), cardiac morbidity and mortality in high risk patients (26,51,64,80,81), postoperative pain and increased consumption of analgesics (18,72,74,78,(82)(83)(84)(85)(86), postoperative delirium(87), patient dissatisfaction (88)(89)(90)(91), increased hospital length of stay (29,89,92) and these in turn can incur a signi cant health care cost (1,86,89,92).…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in India revealed that the prevalence of preoperative anxiety was varied from 47-70.3% (27)(28)(29) while the prevalence of preoperative anxiety in Pakistan was ranged from 62-97% (16,22,30).…”
mentioning
confidence: 99%
“…[ 2 ] Perioperative anxiety has been reported to be affected by various factors, including socio-demographic characteristics (age, gender, socioeconomic status, education level, marital status, mental diseases, past anesthesia exposure) and clinical factors (type and complexity of surgery, chronicity of disease, and nature of procedure). [ 3 5 ] Also, it was shown that perioperative anxiety can be ameliorated by providing preoperative education to the patients, [ 6 ] adequate provision of information before the procedure, [ 7 ] and anxiolytic medicines.…”
Section: Introductionmentioning
confidence: 99%